2017
DOI: 10.1186/s12863-017-0485-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative profiling of hepatopancreas transcriptomes in satiated and starving Pomacea canaliculata

Abstract: BackgroundAlthough Pomacea canaliculata is native to South and Central America, it has become one of the most abundant invasive species worldwide and causes extensive damage to agriculture and horticulture. Conventional physical and chemical techniques have been used to eliminate P. canaliculata, but the effects are not ideal. Therefore, it is important to devise a new method based on a greater understanding of the biology of P. canaliculata. However, the molecular mechanisms underlying digestion and absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…canaliculata has revealed expanded cellulase gene families, which may give rise to increased gut enzyme versatility found in this study. It has also been shown that cellulose expression is influenced by the feeding state (i.e., satiated or starved) of apple snails . In addition, cellulases A0A2T7PPN6 (GHF9), A0A2T7NYY1 (GHF10), A0A2T7NZR0 (GHF10), and Pc89752 (GHF10) were uniquely found in the digestive contents indicating a possible origin in unicellular glands of the gut or in commensal symbiotic organisms .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…canaliculata has revealed expanded cellulase gene families, which may give rise to increased gut enzyme versatility found in this study. It has also been shown that cellulose expression is influenced by the feeding state (i.e., satiated or starved) of apple snails . In addition, cellulases A0A2T7PPN6 (GHF9), A0A2T7NYY1 (GHF10), A0A2T7NZR0 (GHF10), and Pc89752 (GHF10) were uniquely found in the digestive contents indicating a possible origin in unicellular glands of the gut or in commensal symbiotic organisms .…”
Section: Discussionmentioning
confidence: 99%
“…Two different quantitative profiles were found in digestive gland: representatives from GHF2 (glucuronidases and mannosidases) and GHF3 (xylosidases) showed higher tissue values than contents while representatives from GHF5 (mannosidases), 10 (xylanases), and 16 (β-1,3-glucanases) families showed lower tissues values than contents. It is possible that the digestive gland expressed different hemicellulase isoforms which are associated with the ingested food types or the feeding state of the snails; however, future research will have to clarify this point. Mannosidases from GHF38 were detected in the salivary glands, but these peptides might be overestimated since this tissue showed about 7× less soluble proteins compared to other tissues and the samples were normalized by protein load prior to digestion and analysis.…”
Section: Discussionmentioning
confidence: 99%
“…digestive and reproductive tissues). Few studies outside of Drosophila have utilized nextgeneration methods to measure gene expression throughout starvation (but see Khudyakov et al, 2015a,b;Yang et al, 2017). In whole-body studies on Drosophila, ∼25% of the genome had coding sequences with differential transcription during starvation (Harbison et al, 2005), underscoring the significant biological shifts necessary under food limitation.…”
Section: Mechanisms Responses and Traits Affected By Repeated Starvamentioning
confidence: 99%
“…It is possible that the higher structural and functional diversity of serine peptidases is influenced by the feeding state (satiated or starved) of apple snails and their ability to select among different macrophytes 24,69 . The feeding rate of macrophytes with higher nitrogen and phosphorus content positively influences eggs production and growth in P. canaliculata ; however, these parameters may decrease when snails consume plants with high phenolic content and/or physical and chemical defences 69 .…”
Section: Discussionmentioning
confidence: 99%
“…The diversity, origin, and characterization of digestive enzymes have been highlighted recently in invasive ampullariids because they are essential for the digestion of different food sources of macronutrients 7,16–22 . These enzymes include a set of genetically codified enzymes, as well as enzymes plausibly secreted by symbiotic bacteria 16,23,24 . Salivary and digestive glands of P. canaliculata are involved in the synthesis and secretion of glycosidases (i.e.…”
Section: Introductionmentioning
confidence: 99%